A Nanostrategy for Efficient Imaging‐Guided Antitumor Therapy through a Stimuli‐Responsive Branched Polymeric Prodrug. Issue 6 (31st January 2020) - Cai, Hao; Dai, Xinghang; Wang, Xiaoming; Tan, Ping; Gu, Lei; Luo, Qiang; Zheng, Xiuli; Li, Zhiqian; Zhu, Hongyan; Zhang, Hu; Gu, Zhongwei; Gong, Qiyong; et al.
Abstract: A stimuli‐responsive polymeric prodrug‐based nanotheranostic system with imaging agents (cyanine5.5 and gadolinium‐chelates) and a therapeutic agent paclitaxel (PTX) is prepared via polymerization and conjugating chemistry. The branched polymeric PTX‐Gd‐based nanoparticles (BP‐PTX‐Gd NPs) demonstrate excellent biocompatibility, and high stability under physiological conditions, but they stimuli‐responsively degrade and release PTX rapidly in a tumor microenvironment. The in vitro behavior of NPs labeled with fluorescent dyes is effectively monitored, and the NPs display high cytotoxicity to 4T1 cells similar to free PTX by impairing the function of microtubules, downregulating anti‐apoptotic protein Bcl‐2, and upregulating the expression of Bax, cleaved caspase‐3, cleaved caspase‐9, cleaved‐PARP, and p53 proteins. Great improvement in magnetic resonance imaging (MRI) is demonstrated by these NPs, and MRI accurately maps the temporal change profile of the tumor volume after injection of NPs and the tumor treatment process is also closely correlated with the T 1 values measured from MRI, demonstrating the capability of providing real‐time feedback to the chemotherapeutic treatment effectiveness. The imaging‐guided chemotherapy to the 4T1 tumor in the mice model achieves an excellent anti‐tumor effect. This stimuli‐responsive polymeric nano‐agent opens a new door for efficient breast cancer treatment under the guidance of fluorescence/MRI. Abstract : This study demonstrates a strategy to fabricate stimuli‐responsive branched polymeric prodrug‐based theranostic nanomedicine. The anticancer mechanism is studied well and the in vitro and vivo behaviors including biodistribution, retention, and anticancer efficacy can be monitored well by imaging. This stimuli‐responsive polymeric demonstrates great potential of a platform for cancer nanotheranostics.